Relationship of Organizational Skills to the Mental Exhaustion of Work-from-Home Employees of BPO Companies: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research aimed to determine whether organizational skills and mental exhaustion were correlated in BPO organizations that employ home workers. The Snowball sampling technique selected 100 participants from various companies in Quezon City. To determine if there was a relationship between organizational skills and mental exhaustion of work-from-home employees in BPO companies, this study used a Quantitative Correlation design – snowball sampling and a self-made questionnaire, dependent and independent Likert Scale. The study discovered an inverse correlation between the two variables, indicating that working from home benefited employees by improving organizational skills. Additionally, they improved their work abilities and performance. As a result, the study concluded that working from home was more acceptable among BPO employees.